Paradigma Masyarakat Muslim Dalam Membentuk Konsep Pendidikan Islam - Shopiah Syafaatunnisa; Andewi Suhartini (Oasis : Jurnal Ilmiah Kajian Islam, 2024)
This study aims to explore the role of the Bayani, Burhani, and Irfani paradigms in shaping a holistic and adaptive concept of Islamic education. These three paradigms—Bayani, which emphasizes religious texts; Burhani, which emphasizes logic and rationality; and Irfani, which focuses on intuition and inner understanding—are complementary epistemologies within Islam. The study employs a qualitative method with a literature review approach, where various relevant sources are analyzed in depth to understand how these paradigms can be integrated to develop an Islamic education system that meets modern challenges while preserving fundamental Islamic values. The findings indicate that the integration of the Bayani, Burhani, and Irfani paradigms produces an Islamic education concept that is not only relevant to contemporary contexts but also supports the holistic development of students' intellectual, emotional, and spiritual character. Through this integration, Islamic education can serve as a foundation for developing an adaptive, inclusive educational system aligned with Islamic identity.